Budidaya Alpukat Siger Sebagai Produk Unggulan Desa Karang Binangun 2 - Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2025)
Siger avocado cultivation is an alternative horticultural commodity development that has the potential to increase the income of rural communities. Karang Binangun 2 Village has agro-climatic conditions that support the development of Siger avocados, such as land availability, sufficient rainfall, and soil characteristics suitable for avocado growth. This study aims to analyze the opportunities and potential of Siger avocado cultivation in Karang Binangun 2 Village as an effort to improve the community's economy. The methods used include field observations, interviews with farmers, and literature studies related to Siger avocado cultivation techniques. The results of the study indicate that Siger avocados have advantages in terms of high productivity, a relatively fast fruiting period, and increasing market demand. However, there are several obstacles faced, including limited farmer knowledge regarding appropriate cultivation techniques and post-harvest management. Therefore, technical assistance, strengthening farmer group institutions, and an integrated marketing strategy are needed so that Siger avocado cultivation can develop sustainably and become a superior village commodity.